Civilian Attitudes Toward the Military through the Prism of Personal Experience in Wartime Ukraine - Klymanska, Larysa; Malachivska-Danchak, Maryana; Klimanska, Maryna; Haletska, Inna (Journal of Education Culture and Society, 2024)
Aim. The goal of the research is psychological analysis as well as the development of the typology of attitude of the civilians of Ukraine toward military personnel in wartime.Methods. The transcripts of five focus group discussions in five cities of different regions of Ukraine have been subjected to thematic analysis. The criteria for analysis were: a) the quality of contacts, b) regularity (frequency) of contacts with military personnel.Results. Four types of attitudes of civilians toward military personnel have been identified: “interaction participant” as a real and personalised contact; “interested witness” as real and close irregular contacts; “observer” as a distant and imaginary irregular contact; “re-teller” as a remote, imaginary contact through accidental meetings. Topics for analysis include emotional treatment, attitudes depending on military personnel types, interaction formats and conflict probability, and the associative image of a military man.Conclusion. The identified attitudes of civilians to military personnel reflect the availability of a dichotomy between the sense of gratitude to military personnel for their heroism vs the striving of civilians to have their own normal life. Proximity to one of the poles determines the type of treatment of military personnel, and, at the same time, the prospective probability and tension of the conflict.Originality. The study was conducted in September-October 2023, the second year of the full-scale Russian invasion of Ukraine. Psychological analysis of the subjective attitude of civilians to military personnel in the social and psychological context of war has been made through focus group discussions.